Suicide risk among prisoners in French Guiana: prevalence and predictive factors - Gülen Ayhan (BMC Psychiatry, 2017)
Abstract Background Suicide rates in prison are high and their risk factors are incompletely understood. The objective of the present study is to measure the risk of suicide and its predictors in the only prison of multicultural French Guiana. Methods All new prisoners arriving between September 2013 and December 2014 were included. The Mini International Neuropsychiatric Interview (MINI) was used and socio-demographic data was collected. In order to identify the predictors of suicide risk multivariate logistic regression was used. Results Of the 707 prisoners included 13.2% had a suicidal risk, 14.0% of whom had a high risk, 15.1% a moderate risk and 41.9% a low risk. Predictive factors were depression (OR 7.44, 95% CI: 3.50–15.87), dysthymia (OR 4.22, 95% CI: 1.34–13.36), panic disorder (OR 3.47, 95% CI: 1.33–8.99), general anxiety disorder (GAD) (OR 2.19, 95% CI: 1.13–4.22), men having been abused during childhood (OR 21.01, 95%, CI: 3.26–135.48), having been sentenced for sexual assault (OR 7.12, 95% CI: 1.98–25.99) and smoking (OR 2.93, 95%, CI 1.30–6.63). Conclusion The suicide risk was lower than in mainland France, possibly reflecting the differences in the social stigma attached to incarceration because of migrant populations and the importance and trivialization of drug trafficking among detainees. However, there were no differences between nationalities. The results reemphasize the importance of promptly identifying and treating psychiatric disorders, which were the main suicide risk factors.